Molecular Dynamics Simulation of Thermal and Irradiation Creep Behavior of FeCrAl Alloy for Nuclear Fuel Cladding - Bei CAO; Wenxiu BAI; Huan YAO; Junmei WU; Chunyu YIN; Ping CHEN (南方能源建设)
[Objective] FeCrAl alloys have shown promise as candidate materials for accident tolerance fuel cladding because of their excellent high-temperature strength, irradiation resistance, and mature fabrication technology. There are fewer studies related to the thermal and irradiation creep of FeCrAl alloys due to the high cost, long cycle time and difficult testing of neutron irradiation. The thermal and irradiation creep behavior of FeCrAl alloys were examined. And, the effects of irradiation dose rate, temperature and stress on the creep rate and parameters of the creep constitutive equations were analyzed. [Method] The creep simulations were performed on several FeCrAl samples with different grain sizes over a wide range of temperature, stress, and irradiation dose rates, using LAMMPS molecular dynamics simulator. [Result] The results show that the irradiation creep rate is significantly lower, compared to the thermal creep rate. As stress rises, the thermal creep rate increases exponentially, and the stress exponent increases roughly from 0.9 to 2.0 at the turning point of 0.8 GPa. The irradiation creep rate increases linearly with stress and dose rate, that is, the exponents of both dose rate and stress for irradiation creep are very close to 1.0. Besides, higher temperatures accelerates the linear increase of irradiation creep rate with dose rate, and the irradiation creep pre-factor becomes larger. [Conclusion] The creep of FeCrAl alloys under conditions of high temperature and irradiation is mainly attributed to the thermal creep behavior. Higher temperatures and stresses accelerate the irradiation creep process.